Regional Reconstruction of Orbital Exenteration Defects - Jategaonkar, Ameya A.; Vernon, Dominic; Byrne, Patrick J. (Seminars in Plastic Surgery, 2019)
Aggressive disease such as invasive fungal infections or malignancies may necessitate orbital exenteration. The defects of orbital exenteration are often complex involving adjacent structures. Rehabilitation of the orbital exenteration defect poses unique challenges to the reconstructive surgeon. Various options have been described ranging from secondary intention to microvascular free tissue reconstruction. Here the authors review local/regional options for reconstruction of orbital exenteration defects.
Keywords: regional reconstruction; skin graft; temporalis; pericranial flap